2022
DOI: 10.1038/s41598-022-16915-8
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation parameters abnormalities and their relation to clinical outcomes in hospitalized and severe COVID-19 patients: prospective study

Abstract: There has been growing attention toward the predictive value of the coagulation parameters abnormalities in COVID-19. The aim of the study was to investigate the role of coagulation parameters namely Prothrombin concentration (PC), activated Partial thromboplastin Time (aPTT), D-Dimer (DD), Anti Thrombin III (ATIII) and fibrinogen (Fg) together with hematological, and biochemical parameters in predicting the severity of COVID-19 patients and estimating their relation to clinical outcomes in hospitalized and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
1
11
2
1
Order By: Relevance
“…According to the results, it was noted that deaths were observed only in the severe group. In the study conducted by Esmaeel et al, 33 ROC analysis and predictive values were noted for the prediction of the group in which the disease was severe and deaths occurred, and it was observed that AUC = 0.940, sensitivity 76.0%, and specificity 93.0% at d-dimer 2.0 ng/L cut-off value ( P < .001). Our study was conducted with a larger sample size of 498 patients and included patients with both PCR positivity and COVID-related thorax CT involvement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the results, it was noted that deaths were observed only in the severe group. In the study conducted by Esmaeel et al, 33 ROC analysis and predictive values were noted for the prediction of the group in which the disease was severe and deaths occurred, and it was observed that AUC = 0.940, sensitivity 76.0%, and specificity 93.0% at d-dimer 2.0 ng/L cut-off value ( P < .001). Our study was conducted with a larger sample size of 498 patients and included patients with both PCR positivity and COVID-related thorax CT involvement.…”
Section: Discussionmentioning
confidence: 98%
“…In 2021, in a study conducted on 267 COVID-19 patients, Esmaeel et al 33 compared biochemistry and coagulation parameters on disease severity and investigated their relationship with mortality. In the study, PCR positivity was taken as the diagnostic criteria for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ndings indicated that there is a signi cant and direct correlation between IL-6 and CRP and D-dimer, although a negative and signi cant correlation was observed between HIF-1α and D-dimer, IL-6 and CRP. It has been shown that coagulation disorders are present in patients with COVID-19 (10); under these conditions, the activity of the brinolytic system is increased, and D-dimer is formed from brin (11). Thus, increasing the level of D-dimer is an indicator for coagulation disorders associated with COVID-19 infection (11,12), and it has been shown that the level of D-dimer is signi cantly elevated during COVID-19 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Koagülasyon parametrelerinin değerlendirildiği bir derlemede aPTT ve PLT değerleri mortalite için öngörücü bulunmuş, fibrinojen yüksekliğinin YB'a yatış ile ilişkisi belirlenmiştir (24). Literatürde araştırma sonucumuza benzer şekilde, aPTT, fibrinojenin prognozda öngörücü olmadığını değerlendiren çalışmalar da bulunmaktadır (1,19,25). (1,20).…”
Section: Gereç Ve Yöntemlerunclassified